The Effect of Internal and External Obstacles to Growing and Developing Stone and Marble Industry Sector in Palestine - Jaradat, Nasser; Thawabteh, Aysha (The Arab Journal of Administration, 2021)
The study aims to Identify the effect of internal and external obstacles to growing and developing stone and marble industry sector in Palestine. Independent internal variables consider as (management, strategic planning, building organizational level, capital, competitiveness and information systems) and external factors (infrastructure, exporting, and the administered laws and regulations) to examining the impact on the dependent variable, i.e., growing and developing stone and marble industry sector in Palestine. The study employs descriptive analytical approach. The study examines the stone and marble factories (totalling 618). A random sample was selected for the study population (totalling 140). The questionnaires were then distributed to 140 persons, but only valid 107 ones were studied for statistical analysis. The findings of internal obstacles show that management and strategic planning; building organizational level, capital and the administered laws and regulations have all positive impact on growing and developing stone and stone and marble industry sector in Palestine. The study, however, shows that competitiveness has no impact on developing stone and marble industry sector in Palestine. As for analysis of external obstacles, the study reveals that infrastructure has an impact on growing and developing stone and marble industry sector in Palestine. As for exporting and the administered laws and regulations, the study shows that there is no impact whatsoever. In the light of findings, the study makes a number of recommendations, the most important of which is that running stone and marble factories should be within a strategic plan, building organizational level, cooperation with ad hoc bodies and banks to facilitate banking services for the owners of the factories and train the employees in these factories to use information systems, offer some incentives for foreign donors to build industrial zones and infrastructure suitable for stone and marble industry.